Combined time and energy optimal trajectory planning with quadratic drag for mixed discrete-continuous task planning. (2nd January 2019) - Taitler, Ayal; Ioslovich, Ilya; Gutman, Per-Olof; Karpas, Erez
ABSTRACT: The problem of mixed discrete-continuous task planning for mechanical systems, such as aerial drones or other autonomous units, can be often treated as a sequence of point-to-point trajectories. In this work, the problem of optimal trajectory planning under a combined completion time and energy criterion, for a straight point to point path for a second-order system with quadratic under state (velocity) and control (acceleration) constraints is considered. The solution is obtained and proved to be optimal using the Pontryagin Maximum Principle. Simulation results for different cases are presented and compared with a customary numerical optimal control solver.